2017
DOI: 10.1007/s40544-017-0145-y
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation and prediction of wear behavior of cotton fiber polyester composites

Abstract: Abstract:The cotton fiber reinforced polyester composites were fabricated with varying amount of graphite fillers (0, 3, 5 wt.%) with a hand lay-up technique. Wear tests were planned by using a response surface (Box Behnken method) design of experiments and conducted on a pin-on-disc machine (POD) test setup. The effect of the weight percentage of graphite content on the dry sliding wear behavior of cotton fiber polyester composite (CFPC) was examined by considering the effect of operating parameters like load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…[31] The NaOH treated and untreated fiberreinforced composites were analyzed for their tribological behavior and found that the more influential factors are in the order of load, speed, and sliding distance. [32] From the experimental investigation of abrasive wear for Ipomoea epoxy composites filled with particulates, it was found that the rate of wear decreased gradually with the increase in sliding distance and reached saturation when F I G U R E 1 (A) Calotropis plant; (B) stems; and (C) raw fiber extracts multiple passes were given. Ramie fiber reinforced epoxy composites were subjected to tribological behavior analysis, specifically CoF, and it was found that they had undergone an increase in CoF when the applied load on the fiber increased.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[31] The NaOH treated and untreated fiberreinforced composites were analyzed for their tribological behavior and found that the more influential factors are in the order of load, speed, and sliding distance. [32] From the experimental investigation of abrasive wear for Ipomoea epoxy composites filled with particulates, it was found that the rate of wear decreased gradually with the increase in sliding distance and reached saturation when F I G U R E 1 (A) Calotropis plant; (B) stems; and (C) raw fiber extracts multiple passes were given. Ramie fiber reinforced epoxy composites were subjected to tribological behavior analysis, specifically CoF, and it was found that they had undergone an increase in CoF when the applied load on the fiber increased.…”
Section: Introductionmentioning
confidence: 99%
“…[31] The NaOH treated and untreated fiberreinforced composites were analyzed for their tribological behavior and found that the more influential factors are in the order of load, speed, and sliding distance. [32] From the experimental investigation of abrasive wear for Ipomoea epoxy composites filled with particulates, it was found that the rate of wear decreased gradually with the increase in sliding distance and reached saturation when…”
Section: Introductionmentioning
confidence: 99%
“…Wear is acceptably predicted by regression models and ANNs model. 10 Dry friction wear testers determine abrasive wear levels. ANNs and particle swarm optimization (PSO) based prediction tools estimates tribological and mechanicalproperties; such as abrasion resistance, impact energy, tensile modulus and hardness; of the composites.…”
Section: Introductionmentioning
confidence: 99%
“…14 One of the main obstacles associated with applications of ANNs to physical processes like wear is the difficulty of explaining functional interrelations (between the wear rate and the physical variables governing the process) as they are predicted by ANN approximations. 15,16 To address this so-called ''black box'' issue of ANN modeling approach, a number of problem-specific ANN-based models of hybrid type have been developed. [17][18][19] In the present paper, we consider the main problem associated with the application of multilayer perceptron (MLP) for analyzing experimental data obtained from pin-on-disk sliding wear tests.…”
Section: Introductionmentioning
confidence: 99%
“…14 One of the main obstacles associated with applications of ANNs to physical processes like wear is the difficulty of explaining functional interrelations (between the wear rate and the physical variables governing the process) as they are predicted by ANN approximations. 15,16…”
Section: Introductionmentioning
confidence: 99%